The Creative Transformation of Public Criticism in Indonesia: A Ricoeurian Discourse Analysis of Kiky Saputri’s Roasting Performance - Abdul Pirol; Aswan Aswan (DISCOURSE: Indonesian Journal of Social Studies and Education, 2026)
This article examines the creative transformation of public criticism in Indonesia through the case study of comedian Kiky Saputri’s roasting of political figures in the television program Lapor Pak. In a socio-political environment characterized by a low tolerance for dissent, the study applies Paul Ricoeur’s three-stage hermeneutic model prefiguration, configuration, and transfiguration to analyze how political critique is reshaped through humor and storytelling. The findings reveal that roasting serves as a discursive strategy that shifts criticism from confrontational protest to a narrative form that blends satire, entertainment, and public engagement. This transformation aligns with Ricoeur’s concept of semantic autonomy, in which the meaning of a text is determined by its audience rather than its origin. While roasting opens a space for creative dissent, the study also identifies its potential for depoliticization as it becomes embedded within commercial entertainment logics. Thus, the transformation of criticism into popular media content reflects both discursive innovation and ideological tension in contemporary Indonesian public life.